Etika Auditor Sebagai Variabel Moderasi pada Pengaruh Kompetensi, Independensi dan Moral Reasoning Terhadap Kualitas Audit - Dirk Berly Tehuayo; Arthur Reinaldo Tanihatu (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
The research aims to empirically test the competency, independence and moral reasoning of auditors on audit quality with auditor ethics as a moderating variable at the Representative BPKP of maluku province. The sample in this study were all auditors who worked at the Maluku Province Representative Financial and Development Supervisory Agency, totaling 60 auditors using a questionnaires survey method and measured using a likert scale. The number of questionnaires distributed was 60 questionnaires, and 56 questionnaires were returned. The results of this research show that partially, competency, independence, and moral reasoning have a positive effect on audit quality. Tests using Moderated Repression Analysis (MRA) show that auditor ethics are able to moderate the relationship between competence, independence and moral reasoning and audit quality.